2012
DOI: 10.1074/jbc.m112.383596
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Catalytic Site of Phospholipase D2 (PLD2) Newly Described Guanine Nucleotide Exchange Factor Activity

Abstract: Background: Phospholipase D2 harbors a newly described GEF activity. Results: The domains and residues responsible for the GEF activity of PLD2 and their physiological relevance in vivo have been identified. Conclusion:The catalytic site makeup provides a new mechanism of action. Significance: Significance of the PX domain in Rac2GEF activity of PLD2 is shown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…PLD2 is a newly discovered GEF for Ras and Rac2 (GomezCambronero, 2011;Henkels et al, 2013;Mahankali et al, 2012;Mahankali et al, 2011b). Another study also demonstrated PLD2's GEF activity towards RhoA (Jeon et al, 2011).…”
Section: Introductionmentioning
confidence: 98%
“…PLD2 is a newly discovered GEF for Ras and Rac2 (GomezCambronero, 2011;Henkels et al, 2013;Mahankali et al, 2012;Mahankali et al, 2011b). Another study also demonstrated PLD2's GEF activity towards RhoA (Jeon et al, 2011).…”
Section: Introductionmentioning
confidence: 98%
“…3 H]butanol as previously described (24)(25)(26). Approximately 50 g of cell sonicates was added to microcentrifuge Eppendorf tubes containing the following assay mix (120-l final volume): 3.5 mM PC8 phospholipid, 1 mM PIP2, 75 mM HEPES, pH 7.9, and 2.3 Ci (4 mM) of [ 3 H]butanol.…”
mentioning
confidence: 99%
“…The PX domain of PLD2 contains the site for GEF activity, whereas both the PLD2-PX and -PH domains are involved in interacting with the small GTPase substrate (24), which can be either Rac2 or Ras (22,25). …”
Section: Introductionmentioning
confidence: 99%